2009
DOI: 10.1071/sr08088
|View full text |Cite
|
Sign up to set email alerts
|

Fate of potassium fertilisers applied to clay soils under rainfed grain cropping in south-east Queensland, Australia

Abstract: Negative potassium (K) balances in all broadacre grain cropping systems in northern Australia are resulting in a decline in the plant-available reserves of K and necessitating a closer examination of strategies to detect and respond to developing K deficiency in clay soils. Grain growers on the Red Ferrosol soils have increasingly encountered K deficiency over the last 10 years due to lower available K reserves in these soils in their native condition. However, the problem is now increasingly evident on the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Also in other geographical regions negative K balances in agricultural production systems have been reported urging for intensified research efforts on K management and dynamics in different soil types, climatic regions and cropping systems (e.g. Bedrossian and Singh 2004;Bell et al 2009). Greatly increased crop yields and nutrient off-take in harvested products have exacerbated this situation.…”
Section: Introductionmentioning
confidence: 99%
“…Also in other geographical regions negative K balances in agricultural production systems have been reported urging for intensified research efforts on K management and dynamics in different soil types, climatic regions and cropping systems (e.g. Bedrossian and Singh 2004;Bell et al 2009). Greatly increased crop yields and nutrient off-take in harvested products have exacerbated this situation.…”
Section: Introductionmentioning
confidence: 99%
“…Bell et al . reported that soil solution K values varied by 6–7 fold in different soil types despite similar exchangeable K contents 19 , so it can be concluded that measures of K intensity and quantity differ greatly across soils with varying soil properties. In particular, soil clay content influence the K levels observed in different extraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in fertilized K treatments, the K-specific adsorption sites may become saturated with K, with subsequent K fertilization resulting in leaching of surplus K into subsoils. Bell et al (2009) support K determination in their soils at deeper depths than those usually considered to account for these aspects. In Alabama, USA, Cope (1981) summarized 50 years of K fertilization in four sandy low CEC (<5 cmol(+) kg -1 ) soils and one silt loam soil with CEC about 10 cmol(+) kg -1 .…”
Section: The Mass-balance Approachmentioning
confidence: 64%
“…Thus, the mass-balance approach appeared to be operating during the first 2 years, but not in the subsequent 4 years. What was not considered by the researchers, but has been observed in Australia (Bell et al 2009) is that K can be extracted by roots from deeper soil layers not measured in traditional soil testing approaches (e.g., the cultivated layer), especially when surface soil K availability is depleted (unfertilized treatments), or leached to deeper soil depths and retained at these depths when surplus K applications are made (Bell et al 2017a, b). In both instances, the surface layer soil K tests may remain relatively unchanged.…”
Section: The Mass-balance Approachmentioning
confidence: 99%